20th Anniversary Ottawa Decision Support Framework: Part 3 Overview of Systematic Reviews and Updated Framework. (April 2020) - Stacey, Dawn; Légaré, France; Boland, Laura; Lewis, Krystina B.; Loiselle, Marie-Chantal; Hoefel, Lauren; Garvelink, Mirjam; O'Connor, Annette
Introduction. The Ottawa Decision Support Framework (ODSF) has guided practitioners and patients facing difficult decisions for 20 years. It asserts that decision support interventions that address patients' decisional needs improve decision quality.Purpose. To update the ODSF based on a synthesis of evidence.Methods . We conducted an overview of systematic reviews, searching 9 electronic databases. Eligible reviews included decisional needs assessments, decision support interventions, and decisional outcome measures guided by the ODSF. We extracted data and synthesized results narratively. Eight ODSF developers/expert users from 4 disciplines revised the ODSF.Results. Of 4656 citations, we identified 4 eligible reviews (>250 studies, >100 different decisions, >50, 000 patients, 18 countries, 5 continents). They reported current ODSF decisional needs and their most frequent manifestations in the areas of inadequate knowledge/information, unclear values, decisional conflict/uncertainty, and inadequate support. They uncovered 11 new manifestations of 6 decisional needs. Using the Decisional Conflict Scale (DCS) to assess decisional needs, average scores were elevated at baseline and declined shortly after decision making, even without information interventions. Patient decision aids were superior to usual care in reducing total DCS scores and improving decision quality. We revised the ODSF by refining definitions of 6 decisional needs and adding new interventions to address 4 needs. We added a decision process outcome and eliminated secondary outcomes unlikely to improve across a range of decisions, retaining the implementation/continuance of the chosen option and appropriate use/costs of health services.Conclusions . We updated the ODSF to reflect the current evidence and identified implications for practice and further research.